Cyclobutane Formation by the Reaction of Ethenesulfonyl Fluoride with Dimethyl Diazomalonate. Issue 39 (13th October 2022) - Li, Le; Mayer, Peter; Ofial, Armin R.; Mayr, Herbert
Abstract: Attempts to synthesize fluorosulfonyl‐substituted pyrazolines by Huisgen reactions (1, 3‐dipolar cycloadditions) of dimethyl diazomalonate with ethenesulfonyl fluoride led to the formation of dimethyl (2 R *, 3 S *, 4 R *)‐2‐(1, 3‐dimethoxy‐1, 3‐dioxopropan‐2‐yl)‐3‐(fluorosulfonyl)‐4‐((fluorosulfonyl)methyl)cyclobutane‐1, 1‐dicarboxylate, a highly substituted cyclobutane derivative, which was characterized by NMR spectroscopy and single crystal X‐ray crystallography. The mechanism of its formation was elucidated by carrying out the reaction at different temperatures and workup conditions. It is shown that an initial 1, 3‐dipolar cycloaddition yields a pyrazoline which extrudes nitrogen with formation of 1‐fluorosulfonyl‐2, 2‐bis(methoxycarbonyl)cyclopropane and dimethyl 2‐(2‐(fluorosulfonyl)ethylidene)malonate, the latter of which dimerized during chromatography on silica gel with formation of the isolated cyclobutane. Abstract : The uncatalyzed 1, 3‐dipolar cycloaddition of ethenesulfonyl fluoride and dimethyl diazomalonate furnished a pyrazoline. Loss of molecular nitrogen during the thermal decomposition of the pyrazoline gave rise to a mixture of a cyclopropane and an isomeric alkylidene malonate. Under alkaline conditions, the CH‐active alkylidene malonate dimerized with formation of a two‐fold fluorosulfonyl‐functionalized cyclobutane.